Multigene phylogeny, morphology, and pathogenicity uncover two novel Globisporangium species (Oomycota) from freshwater habitats in northwestern Iran - Ahadi, Reza; Alizadeh, Alireza; Chenari Bouket, Ali; Masigol, Hossein; Grossart, Hans-Peter (Frontiers in Microbiology, 2025)
During the study of oomycete biodiversity in aquatic environments of northwestern Iran (East Azarbaijan), four Globisporangium isolates were recovered from a river and irrigation canal. These isolates were identified based on multi-locus phylogenetic analyses (ITS, cox1, and cox2 genomic regions) and morphological features. As a result, two novel species were described, namely Globisporangium parvizense sp. nov. and G. sarabense sp. nov., both exhibiting unique sporangial structures and growth patterns. Pathogenicity assays on cucumber seedlings confirmed strains' high potential to cause root and crown rot. This research highlights the diversity of Globisporangium in Iranian freshwater habitats, providing insights into its taxonomy and phylogenetic relationships. Detailed morphological descriptions and illustrations are provided for these novel species.